Nálezy fibronektínu a kolagénu typu IV u lichen ruber planus - Halagovec, Alexander; Baranová, Z (Československá dermatologie, 1998)
The authors examined by immunofluorescence the presence of collagen type IV and fibronectin in a group of nine patients with lichen ruber planus. Collagen iyipe IV was present in the form of granules in the dermis of six patients. Fibronectin was in the region of the dermoepidermal junction at the base of teeth, acanthotic epidermis and the adjacent papillary dermis. As control the authors used 10 specimens of healthy skin from the Clinic of Plastic Surgery in Košice. The authors assume that the mentioned findings of collagen IV and fibronectin reflect damage of the basal membrane zone in lichen ruber planus.
Keywords: Basement Membrane; Collagen; lidé; Fibronectins; bazální membrána; lichen planus; kolagen; Humans; Lichen Planus; fibronektiny